Arab Society Customs in School Found Within Kitab Al Arabiyyah Baina Yadaik - Ritonga, Nur’ainun; Sahyoni, Sahyoni; Nurbayan, Yayan; Burdah, Ibnu; Rahman, Nur Fuadi (Borneo Journal of Language and Education, 2024)
Language and culture are closely intertwined and inseparable. When someone learns a language, they also acquire the values and norms of the community that speaks it. In Arabic language teaching books like Arabiyyah Baina Yadaik, various materials introduce aspects of Arab culture such as social life, education, health, economy, and the environment. The purpose of this study is to investigate the institutional and non-institutional customs within the Arab community in schools as presented in the book "Al Arabiyyah Baina Yadaik Vol. 1a." This research adopts a library research approach, employing a qualitative descriptive method. The primary data source is the material from Kitab Al Arabiyah Baina Yadaik Vol. 1a in Addirasah. Secondary sources include books, previous research, and scientific articles related to the study's title. Data collection techniques primarily involve documentation. The analysis technique used is Content Analysis, which involves analyzing data based on its content. The research findings conclude that indigenous Arab customs in schools, as presented in the seventh theme al-dirasah, can be categorized into two groups: Customary Institutions and Non-Institutions. The Non-Institutional Customs identified include: (1) Referring to educators as Muallim/Muallimah or Mudarris/Mudarrisah, (2) Utilizing library and laboratory facilities during breaks, and (3) Commuting to school by bus or car.